Application of bottom ash from cattle manure combustion for removing fluoride and inactivating pathogenic bacteria in wastewater - Lee, Jae In; Cha, Seung Yeon; Ha, Jae Won; Lee, Chang Gu; Park, Seong Jik (Chemical Engineering Research and Design, 2022)
This study addressed the utilization of bottom ash derived from the combustion of cattle manure (BA-CM) for removing fluoride from industrial wastewater and killing gram-negative (E. coli O157:H7 and S. typhimurium) and gram-positive pathogenic bacteria (L. monocytogenes), and it will ensure both the disposal of solid waste and the purification of water. BA-CM had a pore size corresponding to mesopores (2–50 nm) and a fractal dimension (D) of 2.88. The main elements constituting the BA-CM were calcium (Ca) in the form of Ca5(PO4)3(OH) and CaCO3. The Ca released from BA-CM was helpful for removing fluoride via the formation of CaF2. The fluoride adsorption by BA-CM approached equilibrium after 6 h. The fluoride equilibrium adsorption on to BA-CM was well fitted to the Langmuir model and was calculated to have a maximum adsorption capacity of 112.07 mg/g. At pH 3, the adsorption amount of fluoride was 76.33 mg/g, and as the pH increased to 7, fluoride adsorption decreased to 50.74 mg/g. In the pH range of 7–11, the amount of fluoride adsorbed did not decrease and was maintained (50.53 ± 0.22 mg/g). More than 97% fluoride removal could be achieved using 13.33 g/L of BA-CM. BA-CM treatment effectively inactivated pathogens in the contaminated water. The BA-CM treatment for 4 min achieved 3.77 log CFU/mL and 6.56 log CFU/mL reductions in E. coli O157:H7 and S. typhimurium, respectively. L. monocytogenes exhibited higher resistance to BA-CM than the other pathogens tested, and 30 min was required to achieve a reduction of 6.33 log CFU/mL. BA-CM, obtained from the combustion of cattle manure for energy production, can be used as a value-added material for removing fluoride and disinfecting water contaminated with pathogenic bacteria.
Keywords: % reductions; Bottom ash; Cattle manures; E.coli O157:H7; Fluoride; Fluoride adsorptions; Industrial wastewaters; L.monocytogenes; Pathogenic bacterium; S. typhimurium; Bottom ash; Cattle manure; Disinfection; Fluoride; Pathogenic bacteria